Current regenerative approaches to the treatment of generalized periodontitis in young people (literature review) - O.V Kopchak; I.V. Kovach; Y.V. Litvinova; K.A. Yanishevsky; N.S. Marchenko (Medičnì Perspektivi)
Periodontal diseases are a component of the global burden of chronic morbidity worldwide. The prevalence of periodontitis increases with age, reaching a high at the age of 40, which has increased medical and social importance. In Ukraine the prevalence of periodontal diseases among people aged 19-24 reaches 30%, 25-30 years – more than 60%, and in the age group 35-44 years and older – varies from 92 to 98%. With the generalized form of periodontitis in young people, considerable degradation of periodontal tissues occurs, while treatment measures are mainly ineffective, with a temporary therapeutic effect that only stabilizes the course of disease. The goal of this literature review was to identify innovative approaches to the reparation and regeneration of affected periodontal tissues that could be used as non-invasive treatment modes. The conducted analysis included studies whose findings were published in 52 English- and Ukrainian-language information sources for the period 1985-2022. The literature search was carried out in the PubMed, Scopus, Google Scholar databases and in the electronic catalog of the National Scientific Medical Library of Ukraine. The results of the literature review confirm the considerable potential of cell therapy supplemented with platelet-rich plasma for the formation of new periodontal tissues, which supported their use to promote the regenerative process. In combination with stem cells, platelet-rich plasma provides a considerable increase in the effectiveness of periodontal disease treatment in young people. The literature search was carried out in PubMed databases (327 sources), Scopus (121 sources), Google Academy (16 articles) and in the electronic catalog of the National Scientific Medical Library of Ukraine (89 records). Out of 537, 52 sources were selected for review. Periodontal tissue disease is an actual problem today. According to the data of the analyzed literature, the use of stem cells in dentistry is actively studied, but there are no recommendations and protocols for their use in periodontology. The analyzed scientific sources, the results of which were published in English- and Ukrainian-language sources, aimed at tissue regeneration, have a significant impact on the creation of new approaches to the treatment of generalized periodontitis. The world experience of using cellular technologies with using stem cells demonstrates the significant potential and positive results of their application to promote the regenerative process in the comprehensive treatment of periodontal diseases. The combination of stem cells and platelet-enriched plasma significantly increases the effectiveness of treatment of periodontal tissue diseases, in particular generalized periodontitis in young people. The use of stem cells and growth factors, which contains platelet-rich plasma, allows you to significantly increase the effectiveness of periodontal disease treatment.